Sex difference in ambulatory blood pressure control associates with risk of ESKD and death in CKD patients receiving stable nephrology care. Issue 11 (2nd February 2021) - Minutolo, Roberto; Gabbai, Francis B; Agarwal, Rajiv; Garofalo, Carlo; Borrelli, Silvio; Chiodini, Paolo; Signoriello, Simona; Paoletti, Ernesto; Ravera, Maura; Bellizzi, Vincenzo; Conte, Giuseppe; De Nicola, Luca
Abstract: Background: It is unknown whether faster progression of chronic kidney disease (CKD) in men than in women relates to differences in ambulatory blood pressure (ABP) levels. Methods: We prospectively evaluated 906 hypertensive CKD patients (553 men) regularly followed in renal clinics to compare men versus women in terms of ABP control [daytime <135/85 and nighttime blood pressure (BP) <120/70 mmHg] and risk of all-cause mortality and end-stage kidney disease (ESKD). Results: Age, estimated glomerular filtration rate and use of renin–angiotensin system inhibitors were similar in men and women, while proteinuria was lower in women [0.30 g/24 h interquartile range (IQR) 0.10–1.00 versus 0.42 g/24 h, IQR 0.10–1.28, P = 0.025]. No sex-difference was detected in office BP levels; conversely, daytime and nighttime BP were higher in men (134 ± 17/78 ± 11 and 127 ± 19/70 ± 11 mmHg) than in women (131 ± 16/75 ± 11, P = 0.005/P < 0.001 and 123 ± 20/67 ± 12, P = 0.006/P < 0.001), with ABP goal achieved more frequently in women (39.1% versus 25.1%, P < 0.001). During a median follow-up of 10.7 years, 275 patients reached ESKD (60.7% men) and 245 died (62.4% men). Risks of ESKD and mortality (hazard ratio and 95% confidence interval), adjusted for demographic and clinical variables, were higher in men (1.34, 1.02–1.76 and 1.36, 1.02–1.83, respectively). Adjustment for office BP at goal did not modify this association. In contrast, adjustment for ABP at goal attenuated the increased risk in men for ESKD (1.29, 0.98–1.70) and death (1.31, 0.98–1.77). In the fully adjusted model, ABP at goal was associated with reduced risk of ESKD (0.49, 0.34–0.70) and death (0.59, 0.43–0.80). No interaction between sex and ABP at goal on the risk of ESKD and death was found, suggesting that ABP-driven risks are consistent in males and females. Conclusions: Our study highlights that higher ABP significantly contributes to higher risks of ESKD and mortality in men.